Efforts of Islamic Education Teachers in Fostering Noble Character in elementary Islamic school - Muh. Ibnu sholeh; Siti fatinnah binti Ab Rahman (International Journal of Islamic Education Studies, 2025)
This study aims to analyze the efforts of Islamic Education teachers in fostering noble character among students at MI Fattahul Huda. Character education is considered a fundamental aspect of Islamic education, as it equips young learners not only with cognitive knowledge but also with moral and spiritual values. This research employs a qualitative descriptive method, involving observation, interviews, and documentation to gather comprehensive data about teaching practices and student behavior. The findings reveal that teachers implement character development through modeling good behavior, habituating positive practices, and integrating moral values into learning activities and school culture. Teachers also engage students in religious routines such as prayer, Qur’an recitation, and social activities to strengthen both discipline and empathy. Despite these efforts, challenges arise from the diversity of student backgrounds, limited family involvement, and the influence of technology and social media, which often contradict school values. Teachers overcome these issues by collaborating with parents, reinforcing religious practices, and adopting creative and contextualized teaching methods. This study highlights the novelty of examining teacher strategies in a rural madrasah context, showing how local values and religious traditions influence character-building efforts. The research concludes that consistent, sincere, and context-based approaches by Islamic Education teachers are essential in shaping students’ noble character and ensuring the sustainability of moral education in primary Islamic schools.